Flowering responses of the woodland strawberry to local climate and reduced precipitation along a European latitudinal gradient - De-la-Cruz, Ivan M.; Batsleer, Femke; Bonte, Dries; Diller, Carolina; Izquierdo, José Luis; Still, Sonja; Osorio, Sonia; Posé, David; de la Rosa; Aurora; Vandegehuchte, Martijn L.; Muola, Anne; et al. (Oxford University Press, 2026)
Climate change creates novel environmental conditions that plant species must adapt to. Since plants are finely tuned to the seasonality of their environments, shifts in their phenology serve as some of the most compelling evidence of climate change's impact. Understanding how key fitness-related phenological traits, such as flowering onset, respond to novel environments is crucial for assessing species' plasticity and/or adaptive potential under climate change. Here, we investigated the onset of flowering in Fragaria vesca (woodland strawberry; Rosaceae) by translocating genotypes between four sites along a south-north gradient in Europe, encompassing its entire latitudinal distribution range with varying temperatures, precipitation patterns, and photoperiods. At each site, we included a reduced precipitation treatment using rainout shelters to simulate drought conditions and assess their impact on flowering onset. Our findings revealed that southern and central European genotypes exhibited a delayed onset of flowering when translocated to the northernmost site. In contrast, no difference among genotypes was found in the onset of flowering when grown in more southerly sites. Reduced precipitation accelerated flowering across several sites and all genotypes, irrespective of their latitudinal origin. Overall, northern European genotypes showed a greater capacity to adjust their onset of flowering in response to the different photoperiods and temperatures across the latitudinal gradient compared to southern European genotypes, suggesting that they may be more resilient to shifting environmental conditions. Differences in phenotypic plasticity among genotypes translocated to higher versus lower latitudes highlight the role of photoperiod in evaluating a species' capacity to cope with climate change.